The sugar contents of commercial samples of tobacco leaves - Ram, Jaghat B.
The reducing sugars of the tobacco samples have been determined by the Munson-Walker method. The principle involved in this determination is based in the property of reducing sugar to reduce alkaline tartrate solution of copper sulfate to Cu2O. the weight of the reducing sugar is calculated from Munson-Walker table.